Posterior choroidal fluid loculation in central serous chorioretinopathy presenting as a choroidal elevation: A rare Pachychoroid phenotype. Issue 3 (May 2022) - Manayath, George J; Balan, Reshma; Ranjan, Ratnesh; Saravanan, Veerappan R; Narendran, Venkatapathy
Purpose: To describe an unusual variant of central serous chorioretinopathy (CSC) presenting as a choroidal elevation with subretinal fluid and its response to accepted treatment modalities of CSC. Design: A retrospective case series. Subjects: Six eyes of three patients, two males and one female, with a mean age of 55.3 years, were included in the study. All of them had Pachychoroid features, solitary choroidal elevation and subretinal fluid on optical coherence tomography (OCT); none of the patients had a previous episode of CSC. Methods: Patients were studied with biomicroscopy, ultrasonography, fluorescein angiography and indocyanine green angiography. Systemic evaluation to rule out inflammatory and infective pathologies, and an oncologist referral also was done. Patients were managed in the line of central serous chorioretinopathy, using conservative treatment, focal laser and oral eplerenone. Main outcome measures: Resolution of subretinal fluid and choroidal elevation. Results: Complete resolution of choroidal elevation and subretinal fluid was noted in all the three patients. There was no recurrence till the end of follow-up. Conclusion: Pachychoroid disease may present as solitary choroidal elevation with subretinal fluid due to exaggerated posterior choroidal fluid loculation and has a favourable outcome. However, it should be considered after exclusion of other differential diagnoses.